Association of peanut cultivars and aqueous neem extract in the feeding and development of Spodoptera frugiperda (J. E. Smith) - Boiça Junior, Arlindo Leal; Rodrigues, Nara Elisa Lobato; Janini, Julio Cesar; Bottega, Daline Benites; Sousa, Vitor Quintela; Silva, Anderson Gonçalves da (EntomoBrasilis, 2020)
The current study aimed to test how aqueous neem Azadirachta indica A. Juss. extract affects the attractiveness, feeding and development of Spodoptera frugiperda (J. E. Smith) on different: peanut cultivars. Tests were carried out under laboratory conditions with the cultivars IAC 503 and IAC 147 and aqueous neem extract in concentrations (mass/volume) of 5 and 10%, obtained from seeds and dried in an oven at a temperature of 35 to 38 °C for 15 days, with caterpillars offered a food choice preference test. For this, leaf discs from each treatment were placed in Petri dishes into which three first instar caterpillars were released. To assess resistance biology, single newly-hatched caterpillars were transferred to individual Petri dishes, where the following biological parameters were measured: larval mortality after 1, 3, 5, 7 and 10 days; pupal mortality; total mortality; weight of 10-day-old caterpillars; pupal weight at 24 hours; and adult longevity. The main conclusions of the work, include: cultivar IAC 147 was less attractive and consumed less; cultivar IAC 503 plus 10% neem extract reduced leaf consumption; cultivar type did not affect caterpillar biological development, and 10% neem extract caused 100% mortality in S. frugiperda.